Pengaruh Word Of Mouth, Kualitas Produk, Dan Kepercayaan Merek Terhadap Keputusan Pembelian Skincare Elbyci Di Klaten - Liya Cahya Setyaningrum; Titin Hargyatni (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This study aims toanalyze the influence of Word Of Mouth, Product Quality, and Brand Trust on Purchasing Decisions for Elbyci skincare products in Klaten. The sample in this research was 95 respondents who were consumers of Elbyci skincare in Klaten.The research method uses quantitative with multiple linear regression analysis. The results of this study indicate that Word Of Mouth has a positive and significant effect on purchasing decisions and Product Quality has a positive and significant effect on Purchasing Decisions, while Brand Trust has a positive effect but is not significant to Purchasing Decisions. The three variables simultaneously have a positive and significant effect on Purchasing Decisions with a contribution of 66.8%. This study provides recommendations for distributors to improve marketing strategies and product quality is usefulto improve product purchasing decisions.